Diskresi Penyidik dan Batas Normatif Rehabilitasi Penyalahguna Narkotika dalam Pasal 82 Huruf i Undang-Undang Nomor 20 Tahun 2025 tentang KUHAP - Aldri Christian; Agus Rasyid Chandra Wijaya (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2026)
The codification of Indonesian criminal procedure law through Law Number 20 of 2025 has transformed the legal framework for handling narcotics abusers. Article 82(i) excludes narcotics offenses from the restorative justice mechanism while providing an exception for narcotics users and abusers, thereby introducing a non-penal pathway that has never been regulated in previous criminal procedure codifications. This study aims to analyze the legal framework and normative limits of investigators' discretion in referring narcotics users and abusers to rehabilitation under Law Number 20 of 2025. The research employs a normative juridical method using statutory and conceptual approaches. Primary legal materials consist of Law Number 20 of 2025, Law Number 1 of 2023, and Law Number 35 of 2009, supported by secondary legal materials in the form of scholarly journals and legal doctrines. The analysis is conducted prescriptively through grammatical, systematic, and teleological interpretation. The findings reveal that Article 82(i) merely serves as an entry point for restorative justice eligibility rather than an independent legal basis for rehabilitation. The absence of definitions for narcotics users and abusers, the lack of linkage with Article 80, and the limitation of assessment procedures to women and vulnerable groups cause investigators' discretion to depend on scattered subordinate regulations, resulting in legal uncertainty and disparities in case handling. This study recommends the enactment of implementing regulations that establish criteria for narcotics users, an integrated assessment mechanism, and standards for supervising investigators' discretion to achieve the rehabilitative objectives of the post-codification legal framework.